METAL OXIDES FROM LIKE-HYDROTALCITES MATERIALS MODIFIED WITH Ga3+ AS CATALYSTS FOR ETHYL BIODIESEL SYNTHESIS - Mancini, Marcelo [UNESP]; Coelho, Adonis [UNESP]; Perrone, Olavo M. [UNESP]; Thomeo, Joao C. [UNESP]; Boscolo, Mauricio [UNESP] (Soc Brasileira Quimica, 2017)
The synthesis of like-hydrotalcites materials (layered double hydroxides-LDHs) with molecular formula MgxMy3+(CO3)(OH)(16) 4H(2)O in different ratios Mg2+/M3+ where M3+ is Al3+, Ga3+ or both was carried out by the coprecipitation method to be applied in the transesterification reactions for synthesis of ethyl biodiesel from soybean oil and ethanol. The reactions were processed for 12 hours at 120 degrees C at a molar ratio oil/ethanol (1/20) with 20% (m/m) of the catalyst in relation to the oil mass, and the products were quantified by GC-FID. With the introduction of Ga3+ in the solid, some physicochemical characteristics of LDHs were kept based in the data from X-ray pattern diffraction (XRD), vibrational spectrometry (ATR-FTIR), and scanning electron microscopy (SEM), but changes from thermogravimetric analysis (TGA), superficial area (BET), and the acidity/basicity properties were observed. Typical hydrotalcite with Mg2+/M3+ = 3 was used as reference material and reach 45.1% of biodiesel conversion. Although the best conversion result (77.6%) was reached from the solid without Ga-3 and with Mg2+/M3+ ratio 4/1, there is an interesting correlation between the catalytic activities and the physicochemical properties of the solids with Ga3+ and their respective homologous materials as discussed in this work.
Keywords: ethyl biodiesel; bioenergy; hydrotalcites; metal oxides; heterogeneous catalysis